Urgensi Vaksinasi Covid-19 Sebagai Wujud Implementasi Hifz Al-Nafs (Studi Kasus Pesantren Modern Al-Amanah Junwangi Krian Sidoarjo) - Mochammad Rafly Try Ramadhani; Zuyinatul Munadhiroh; Abu Dzarrin Al-Hamidy (LP2M IAIN kUDUS, 2021)
AbstractPesantren Modern Al-Amanah is a pesantren-based Islamic educational institution located in Junwangi, Krian, Sidoarjo. In this pandemic era, the pesantren has resumed teaching and learning activities. With the number of 2,000 students, the pesantren has designed a variety of preventive and curative measures to suppress the spread of the Covid-19 virus and maintain the safety of the students' souls. One of preventive efforts carried out by pesantren is through a vaccination program in the pesantren environment. The purpose of this article is to find out and describe how Islamic boarding schools view the phenomenon of the Covid-19 pandemic, especially regarding vaccines which are then correlated with the theory of hifz al-nafs in the study of maqasid al-syariah. This study uses a qualitative method through a Participatory Action Research (PAR) approach in the form of interviews with the head of the Covid-19 task force at the Al-Amanah Modern Islamic Boarding School. The results of this study imply that the implementation of vaccination from the maqasid al-syariah point of view is a very urgent matter. In addition, the procurement of Covid-19 vaccination activities has also been proven to be able to prevent Islamic boarding schools from spreading clusters of the Covid-19 virus.